2017
DOI: 10.4049/jimmunol.1601636
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Specific Variation in E-Selectin Ligand Expression among Human Peripheral Blood Mononuclear Cells: Implications for Immunosurveillance and Pathobiology

Abstract: Both host defense and immunopathology are shaped by the ordered recruitment of circulating leukocytes to affected sites, a process initiated by binding of blood-borne cells to E-selectin displayed at target endothelial beds. Accordingly, knowledge of the expression and function of leukocyte E-selectin ligands is key to understanding the tempo and specificity of immunoreactivity. Here, we performed E-selectin adherence assays under hemodynamic flow conditions coupled with flow cytometry and western blot analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 87 publications
1
41
0
2
Order By: Relevance
“…Among the cells of MPS, human circulating monocytes and, to a lesser extent, human blood cDCs and moDCs are the most comprehensively analyzed group in terms of E-selectin ligand activity. In our studies, human classical monocytes (CD14 ++ CD16 − ) showed significantly higher levels of sLe x determinants as compared to intermediate monocytes (CD14 ++ CD16 + ), whereas non-classical monocytes (CD14 + CD16 ++ ) were almost devoid of sLe x expression ( 123 ). Another study compared the trafficking capacity of human monocyte subsets by analyzing their ability to bind to activated endothelial monolayers, and commensurately, classical monocytes showed noticeably higher capability of adhering to reactive endothelium than did non-classical/intermediate monocytes ( 137 ).…”
Section: E-selectin Ligand Activity Displayed By Circulating Mps Subsmentioning
confidence: 53%
See 3 more Smart Citations
“…Among the cells of MPS, human circulating monocytes and, to a lesser extent, human blood cDCs and moDCs are the most comprehensively analyzed group in terms of E-selectin ligand activity. In our studies, human classical monocytes (CD14 ++ CD16 − ) showed significantly higher levels of sLe x determinants as compared to intermediate monocytes (CD14 ++ CD16 + ), whereas non-classical monocytes (CD14 + CD16 ++ ) were almost devoid of sLe x expression ( 123 ). Another study compared the trafficking capacity of human monocyte subsets by analyzing their ability to bind to activated endothelial monolayers, and commensurately, classical monocytes showed noticeably higher capability of adhering to reactive endothelium than did non-classical/intermediate monocytes ( 137 ).…”
Section: E-selectin Ligand Activity Displayed By Circulating Mps Subsmentioning
confidence: 53%
“…While E-selectin receptor/ligand interactions prominently mediate Step 1 events in transmigration for all leukocytes, L-selectin-dependent binding interaction have also been observed to potently mediate human peripheral blood monocyte binding to activated vascular endothelium under shear stress ( 142 – 144 ). Thus, even though the majority of the reports indicates that initial monocyte adhesion to activated endothelial cells is most critically dependent on E-selectin receptor/ligand interactions ( 123 , 145 150 ), distinct interactions were also reported by other authors. The differences have to do with differences in the leukocyte populations under study, variations in the assay conditions employed (i.e., shear stress levels employed, rotatory shear versus fluid shear conditions, temperature, etc.…”
Section: E-selectin Ligand Activity Displayed By Circulating Mps Subsmentioning
confidence: 85%
See 2 more Smart Citations
“…In all mammals, E-selectin is constitutively expressed in microvessels in the bone marrow and skin and is inducibly expressed in endothelial beds at inflammatory sites in response to the cytokines tumor necrosis factor and interleukin-1 (15). Expression of cell-surface sLe X is therefore a prerequisite for extravasation of all mammalian leukocytes and for migration of mammalian hematopoietic stem/progenitor cells to marrow (15)(16)(17). Importantly, whereas sLe X plays a critical role in controlling leukocyte and hematopoietic stem/progenitor cell migration, aberrant expression of this tetrasaccharide by human malignant cells is a critical mediator of cancer metastasis (18 -20).…”
mentioning
confidence: 99%